Drowning in screen time : a lifeline for adults, parents, teachers, and ministers who want to reclaim their real lives - Murrow, David (Salem Books, 2021)
Between Zoom meetings, online classes, social media, gaming, and binge-watching TV series, humans now spend most of their free time submerged in screen life<U+2014>and that<U+2019>s taking a toll on real life. The good news: there is a way back. Bestselling author David Murrow<U+2019>s new book is a rescue plan for parents, adults, teachers, and ministers who want to help others (or themselves) achieve screen-life/real-life balance. Built around five simple parables, Drowning in Screen Time shows you: <U+2022> What screens are doing to your family and relationships <U+2022> Why screen content is so addictive <U+2022> How to find freedom and confidence in real life. Drowning in Screen Time is full of positive, practical ideas that can help you keep your digital head above water.